Force analysis of the explosion-proof structure of a UAV fuel tank based on the fluid structure coupling method - Wang, Chunzhi; Lu, Changbo; Lin, Xufeng; An, Gaojun; Xu, Ximeng; Gan, Yumeng (Frontiers in Materials, 2022)
In this paper, the stress, strain and flow blocking effect of the explosion-proof honeycomb structure of UAV fuel tank are analyzed when it is impacted by continuous fluid caused by explosion, and the main stress concentration areas and overall stress distribution are found out. It simplifies the problem due to the symmetry of the barrier and explosion-proof structure of UAV fuel tank. Taking three-layer superposition model of UAV fuel tank as the research object, the stress and strain of material structure under detonation impact are analyzed by bidirectional fluid-structure coupling method. The simulation results of choke flow of fuel tank structure are obtained, which provides reference for the structural optimization design of honeycomb barrier and explosion-proof material for UAV.